2007
DOI: 10.1093/geront/47.supplement_1.125
|View full text |Cite
|
Sign up to set email alerts
|

Assisted Living Literature Through May 2004: Taking Stock

Abstract: Purpose: This article assesses the state of research on assisted living (AL) from 1989 to May 2004. Design and Methods: We undertook keyword searches for AL research and amplified these with searches of Web sites, conference proceedings, and follow-up inquiries. We annotated and coded the resultant items according to categories reflecting the research methods used and the topics studied. We did additional comparisons for 38 studies with quantitative data that permitted summarizing resident characteristics, set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 28 publications
(18 reference statements)
1
15
1
Order By: Relevance
“…A noteworthy aspect of our findings is that only five persons had experienced relocation in old age, while all 13 had much to tell about the process going on, in their minds and/or in communication with others. According to a recent literature review on relocation to sheltered housing, or assisted living in US terminology, the literature is not consistent and demonstrates negative as well as positive effects (Kane et al 2007). As demonstrated by our findings, it is necessary to be aware of the heterogeneity among older people and the complexity of their needs and expectations.…”
Section: Discussioncontrasting
confidence: 71%
“…A noteworthy aspect of our findings is that only five persons had experienced relocation in old age, while all 13 had much to tell about the process going on, in their minds and/or in communication with others. According to a recent literature review on relocation to sheltered housing, or assisted living in US terminology, the literature is not consistent and demonstrates negative as well as positive effects (Kane et al 2007). As demonstrated by our findings, it is necessary to be aware of the heterogeneity among older people and the complexity of their needs and expectations.…”
Section: Discussioncontrasting
confidence: 71%
“…We feel it is important to explain our decision to combine assisted living entry with nursing home admission as a global "residential care placement" outcome. Due to its emphasis on choice, control, and autonomy, assisted living was formerly positioned as either an appealing alternative to the more hospital style, institutional milieus of nursing homes or as a bridge between home health care and nursing homes (Kane, Chan, & Kane, 2007). Assisted living is often thought of as a care option that is located on a different point of the "long-term care continuum" than nursing homes.…”
Section: Residential Care Placement and Its Implications For Caregiversmentioning
confidence: 99%
“…Currently, AL residences serve more than 1 million older adults, and that number is expected to continue to increase (Arehart-Treichel, 2003). During the past 10 years, an increasing body of AL research has identified a number of issues and concerns related to the care of older adults with dementia in this setting (Hawes, Rose, & Phillips, 1999;R.A. Kane, Chan, & R.L.…”
mentioning
confidence: 99%